An Unusual Case of Penile Prostate Cancer Uncovered by Multiparametric MRI and PSMA-Targeted 18F-DCFPyL PET/CT. (October 2017) - Rowe, Steven P.; Gorin, Michael A.; Chu, Linda C.; Pienta, Kenneth J.; Pomper, Martin G.; Ross, Ashley E.; Macura, Katarzyna J.
Abstract : Abstract: Multiparametric MRI (mpMRI) is currently the test of choice for imaging sites of prostate cancer located within the pelvis. However, molecular imaging with PET radiotracers that bind to prostate-specific membrane antigen is increasingly being used for this purpose and may compliment mpMRI findings. We present a case of a 59-year-old man with elevated postprostatectomy serum prostate-specific antigen level who was found on both mpMRI and prostate-specific membrane antigen–targeted PET to harbor residual prostate cancer in the corpus spongiosum along the proximal urethra.